"The map of race is the map of Richmond": Eviction and the enduring regimes of racialized dispossession and political demobilization. (3rd July 2022) - Howell, Kathryn; Teresa, Benjamin
ABSTRACT: While the immediate correlates of eviction have been investigated at length, little has been done to connect the root causes in policy and planning over more than a century to the current moment of dispossession. This paper uses analysis of historic documents, including plans, newspaper articles and maps, as well as eviction, geographic foreclosure, and other quantitative data and observational data to make an argument for viewing the state of evictions in Richmond as a continuation of longstanding practices of dispossession and disempowerment in Black neighborhoods. We argue that eviction is one of a chain of dispossessions that is both economic and political. We also argue that framing eviction as an individual, rather than a collective, public problem facilitates ongoing marginalization and inaction. Finally, we cannot understand and address Virginia's high eviction rates without examining the roots of the ongoing, racialized dispossession and lack of political power in these communities.